Analysis of the Influence of Leadership, Work Discipline, and Work Motivation on Employee Performance - Muhamad Algan Bioswara; Heri Wijayanto; Diana Pramudya (Golden Ratio of Data in Summary, 2026)
This study aims to analyze the partial effects of leadership, work discipline, and work motivation on the performance of employees at SMPN 3 Ponorogo. The research employs a quantitative approach using an accidental sampling technique. Data were collected through both primary and secondary sources, with questionnaires distributed to 14 employee respondents. The collected data were then analyzed to determine the relationship between each independent variable and employee performance. The findings indicate that leadership has a positive influence on employee performance, as effective leadership can guide and inspire employees to achieve organizational goals. In addition, work discipline significantly contributes to improving performance by ensuring that employees adhere to rules and responsibilities. Work motivation also shows a positive effect, as motivated employees tend to be more productive and committed. Overall, each variable leadership, work discipline, and work motivation individually has a significant and positive impact on employee performance.